Why is so English in Indonesian Cosmetics Advertisements? Deciphering the Commodification of English - Hadi Sampurna; Riskia Setiarini; Dewianti Khazanah; Reni Kusumaningputri; Syamsul Anam (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
This article discusses language commodification in cosmetics advertisements. The vast growing of cosmetics business in Indonesian in the last decade has triggered the rampant of the new brands of cosmetics either products of local Indonesia or of foreign countries. The use of English is obviously visible in the cosmetics advertisements, making it opaque to be distinguished which brands are local and which are international. In this, we investigate the commodification of English in the advertisements of local brands. The method we use is qualitative, through observation and documentation. The selected data are in the form of lexes in the advertisements, gained through billboards, signages, and in-store displays in some malls in Jakarta. We select 7 advertisements of 6 brands. Using Peirce’s triadic model of signs, we obtain that English is employed due to its multifaceted functions. We argue that once in a while Bahasa Indonesian replaces English, for its accentuation and clarity of the message is intended to make. This is because the advertisements are for Indonesian consumers. One salient finding is there is a tendency to use English in the names of brands, particularly to soar up the sense of quality and internationality, in terms of making the brands ready for competing with other international brands penetrating Indonesian markets on a vast scale.